ACE2, TMPRSS2 distribution and extrapulmonary organ injury in patients with COVID-19 (2020)
At the end of 2019, the coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), emerged in China. Currently, it is breaking out globally and posing a serious threat to public health. The typically clinical characteristics of COVID-19 patients were fever and respiratory symptoms, and a proportion of patients were accompanied by extrapulmonary symptoms including cardiac injury, kidney injury, liver injury, digestive tract injury, and neurological symptoms. Angiotensin converting enzyme 2 (ACE2) has been proven to be a major receptor for SARS-CoV-2 and could mediate virus entry into cells. And transmembrane protease serine 2 (TMPRSS2) could cleave the spike (S) protein of SARS-CoV-2, which facilitates the fusion of SARS-CoV-2 and cellular membranes. The mRNA expressions of both ACE2 and TMPRSS2 were observed in the heart, digestive tract, liver, kidney, brain and other organs. SARS-CoV-2 may have a capacity to infect extrapulmonary organs due to the expressions of ACE2 and TMPRSS2 in the cells and tissues of these organs. It seems that there is a potential involvement of ACE2 and TMPRSS2 expressions in the virus infection of extrapulmonary organs and the manifestation of symptoms related to these organs in patients with COVID-19. Here, we revealed the expressions of ACE2 and TMPRSS2 in extrapulmonary organs, and we also summarized the clinical manifestation and the management of extrapulmonary complications in patients with COVID-19.